Inhibitory Effect of Dihydroaustrasulfone Alcohol on the Migration of Human Non-Small Cell Lung Carcinoma A549 Cells and the Antitumor Effect on a Lewis Lung Carcinoma-Bearing Tumor Model in C57BL/6J Mice - Shuo-Chueh Chen; Yi-Chung Chien; Chun-Hsu Pan; Jyh-Horng Sheu; Chih-Yi Chen; Chieh-Hsi Wu (Marine Drugs, 2014)
There are many major causes of cancer death, including metastasis of cancer. Dihydroaustrasulfone alcohol, which is isolated from marine coral, has shown antioxidant activity, but has not been reported to have an anti-cancer effect. We first discovered that dihydroaustrasulfone alcohol provided a concentration-dependent inhibitory effect on the migration and motility of human non-small cell lung carcinoma (NSCLC) A549 cells by trans-well and wound healing assays. The results of a zymography assay and Western blot showed that dihydroaustrasulfone alcohol suppressed the activities and protein expression of matrix metalloproteinase (MMP)-2 and MMP-9. Further investigation revealed that dihydroaustrasulfone alcohol suppressed the phosphorylation of ERK1/2, p38, and JNK1/2. Dihydroaustrasulfone alcohol also suppressed the expression of PI3K and the phosphorylation of Akt. Furthermore, dihydroaustrasulfone alcohol markedly inhibited tumor growth in Lewis lung cancer (LLC)-bearing mice. We concluded that dihydroaustrasulfone alcohol is a new pure compound with anti-migration and anti-tumor growth activity in lung cancer and might be applied to clinical treatment in the future.